6MH Fish's Enterprise / Muhd Izzuddin Ganih... [et al.] - Ganih, Muhd Izzuddin; Ramli, Mohd Syafiq; Nyanggau, Hendrayanto; Add. Latip, Mohd Fakri Ashraf; Mohd Don, Mohd Hafiez; Awang, Mohd Imranuddin; Suardi, Mohd Safwan (2017)
6MH FISH'S is a kind of business that supply and rearing the freshwater fish which is catfish and tilapia fish. 6MH FISH'S will establish at KG. Sangkir Jalan Kudat, 89158 Kota Belud Sabah. The location is believed to be very strategic for the company to stand as we are targeting the people around Kota Belud area also around Kota Kinabalu area. This business is seen too able to gain the attention of the community and potentially gets the customer demand. In Malaysia, there is still lack of company that dare to rear the freshwater fish and be a big supplier. By be a supplier of freshwater fish, the people in city area easily can get this product without let them find the supplier of interior. Therefore, we are prepared to go through any risk and problem that may encounter during the process of commercializing our product.